Effects of environmental filtering on taxonomic and functional diversity patterns: When spiders and plants provide complementary information to water level management in the Seine estuary - Aurélien Ridel; Markus Neupert; Althéa Cadro; Julio Pedraza; Michael Aubert; Estelle Langlois; Julien Pétillon (Ecological Indicators)
In the Seine estuary in northern France, many artificial structures limit the effect of the tide on associated alluvial zones. Consequently, this affects natural environmental filtering mechanisms linked to tidal regimes and water salinity, which directly influences the structure of organism assemblies in adjacent ecosystems. Here, we propose to study the influence of these filters’ modifications on spiders and plants, two compartments recognized as complementary in terms of bioindication. However, this complementarity has only been studied to a limited extent and rarely in estuarine environments. To highlight this complementarity, we studied the taxonomic and functional patterns obtained across different topographical levels of two sites with contrasting water level managements. Moreover, particular attention was paid to the influence of the weight attributed to rare species (Q order) to shed light on processes affecting species dominance dynamics between taxa. Overall, spider communities appeared less influenced by environmental filtering than plants on both study sites, with taxonomic and functional diversity both demonstrating a low sensitivity to salinity. Spider community assemblies also demonstrated compositional shifts across study sites, mainly driven by changes in abundance and dominance. In contrast, plant communities appeared more sensitive to environmental constraints and water level management, with responses in terms of composition and species turnover rather than unbalanced abundance, suggesting responses at distinct spatial scales between plant and spider communities.